Study on Heat and Flow Behaviors in Heat sinks for Thermoelectric Cooling Module by CFD - Hommalee, Chootichai; วิริยะศาสตร์, อ.ดร.สงกรานต์; Naphon, Paisarn (Srinakharinwirot University Engineering Journal, 2019)
In this paper, a numerical study on the heat transfer characteristics of various heat sink configurations coupled with thermoelectric cooling module for electronic cooling applications is investigated. Effects of flow channel configurations on the heat transfer and flow behaviors are considered. In the numerical model, the main governing equations of continuity equation, momentum and energy equation are used to analyzed the problem. It can see from the result that the number of fins and size have significant effects on the heat transfer rate which results in thermal performance enhancement. However, the pressure drops also increased. The result obtained from this study are expected to lead to guidelines that will allow the optimum designing heat sink coupled with thermoelectric for electronic cooling applications.